Uso de las tics en el proceso de aprendizaje de la educación ambiental y su incidencia en la profesionalización en la carrera de educación básica Universidad Técnica de Cotopaxi, extensión La Maná, año 2014 - Manzaba Cevallos, Jenny Cecibel (2015)
The insufficient use of ICT in the teaching of the XXI century, causes learning problems is for this reason that the development of an interactive CD that complements reinforcement learning activities in the area of environmental education with essential content for meaningful and interactive learning students raised it agrues in teaching basics of using ICTs The methodology has a character of documentary-bibliographical and descriptive because it made an emphasis on case studies of different issues concerning education and environmental awareness benefiting students of basic education and consequently the society that affects the development of a balanced environment.